The Effectiveness of Acceptance and Commitment Therapy on Empathy and Interpersonal Relationships in Obsessive-Compulsive Patients - Fariba Rahmani; Hossein Gowhari; Masoumeh Jolfai Fotouhi; Sahar Saedi (Iranian Evolutionary Educational Psychology Journal, 2024)
Objective: The purpose of this study was to investigate the efficacy of acceptance and commitment-based treatment on empathy and interpersonal relationships in patients with obsessive-compulsive disorder. Methods: This study employed a semi-experimental research design, utilizing a pre-test, post-test with a control group. The statistical population of the study consisted of all patients with obsessive-compulsive disorder seeking treatment in psychiatric clinics in Tehran in 2022. A total of 30 participants (15 in the experimental group and 15 in the control group) were selected through the accessible sampling method. Data collection tools included the Basic Empathy Scale ((Heinke & Louis, 2009)) and Trust in Close Relationships (Rempel & Holmes, 1986). The intervention, which involved acceptance and commitment-based treatment, was administered over 8 sessions of 90 minutes each, once a week, to the experimental group, while the control group did not receive any training. Data analysis was performed using covariance analysis. Results: The results of multivariate covariance analysis indicated that in the experimental group, there was a significant increase in the mean of empathy scores after the intervention. Similarly, the mean of scores for interpersonal relationships increased after the intervention (P<0.01). Conclusions: The results generally endorse the efficacy of third wave psychotherapies, such as Acceptance and Commitment Therapy (ACT), in relation to emotional and interpersonal consequences.